2020
DOI: 10.1097/mat.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Pump Thrombosis in Patients With Left Ventricular Assist Device

Abstract: Pump thrombosis (PT) is a serious adverse event in patients receiving left ventricular assist devices (LVAD). The study aims to determine whether pump parameters and clinical data may enable early detection of PT. This retrospective study included 88 patients who received an LVAD between 2012 and 2015 among which those with intra-PT were identified. In a propensity score–matched control group observation, time periods were matched with time before thrombosis. International normalized ratio (INR) time in therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…To reduce the selection bias, propensity score matching was applied, which was derived from a non-parsimonous logistic multivariate model. Patients were selected based on one-to-one nearest neighbor matching using a wide range of demographic data, clinical data, and preoperative risk factors 34 to minimize effects of confounding factors. An optimal selection was made among these candidates, resulting in a smaller (15 vs 15 patients) total cohort, but the comparison data sets all have the appearance of a randomized study.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the selection bias, propensity score matching was applied, which was derived from a non-parsimonous logistic multivariate model. Patients were selected based on one-to-one nearest neighbor matching using a wide range of demographic data, clinical data, and preoperative risk factors 34 to minimize effects of confounding factors. An optimal selection was made among these candidates, resulting in a smaller (15 vs 15 patients) total cohort, but the comparison data sets all have the appearance of a randomized study.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the decrease of circadian variations has been associated to thrombotic events, potentially anticipating clinical manifestation by 12±6 days (57). Pump thrombosis can also be observed and managed with the help of log-file analysis of average motor power data (58)(59)(60). A steady decrease of pump flow together with a progressive disappearance of circadian rhythm can be also indicative of GI bleeding and resulting hypovolemia, as shown in Figure 8.…”
Section: Trend Data Analysismentioning
confidence: 99%
“…Not surprisingly, the risk of thrombotic events is inversely related to INR levels with the highest event rate reported for an INR range <1.5 [53]. In addition, it has been demonstrated that LVAD patients developing pump thrombosis spent significantly less time within therapeutic INR range in the 2 months prior to the event compared to those without pump thrombosis [54]. Bridging LVAD patients with subtherapeutic INR levels with heparin treatment may therefore, be considered.…”
Section: Long-term Managementmentioning
confidence: 99%